PUBLISITAS SUMEDANG PUSEUR BUDAYA SUNDA DI DINAS PARIWISATA KEBUDAYAAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Hendryawan, Shofwan; Qori, Aghnia Amalia; Wiganda, Cecep Ari; Nurlaelasari, Meli; Sopandi, Muhamad Rizqy; Fitrianti, Sofia Nur (JRPA - Journal of Regional Public Administration, 2024)
This research aims to examine the publicity of Sumedang puseur Sundanese culture at the Sumedang Regency Tourism, Culture, Youth and Sports Department, things that influence publicity and efforts to overcome things that influence publicity. The method used in preparing this research report is the Qualitative Quality Research method. The sampling technique used is Purposive Sampling, namely a technique for sampling data sources with certain considerations. Four people were used as data sources/informants, namely: Service Secretary, Young Expert Culture Officer, Regional Arts and Culture Analyst (2 people). Meanwhile, in analyzing the data, the Miles and Huberman model was used with the steps: data reduction, data presentation, Conclusion drawing/verification, and triangulation, as well as data validation. Based on the results of the research, it was concluded that the publicity of Sumedang pusuer Sundanese culture at the Sumedang Regency Tourism, Culture, Youth and Sports Department was not running optimally, because there were things that influenced publicity, such as the dimensions of writing publicity material with technical indicators for searching for news and technical news writing which were still less than optimal. To overcome various things that affect existing publicity, efforts that can be made are creating interesting news using existing technical techniques, providing special training to the cultural sector regarding news search and writing techniques so that the news that will be presented will be fresher and more interesting. interesting and adds attraction to the community